Aplikasi Sistem Informasi Pelayanan Masyarakat Rukun Tetangga 02 Kelurahan Kalibaruberbasis Website - Wahyudin Wahyudin; Fredy Rizqi Maulana; Mohammad Faisol; Yolanda Yolanda; Eva Zuraidah (JPM: Jurnal Pengabdian Masyarakat, 2021)
Every member of the community, especially those in the neighborhood area 002, Kalibaru Village, expects a letter of introduction to the neighborhood that can be obtained quickly and accurately. However, until now it has not materialized because it is still using a manual system such as writing on a piece of paper. Often when residents want to take care of the Cover Letter, it must take days, because the schedule of the Head of the Neighborhood Association is not always at home. The purpose of this community service outreach activity is to improve the service quality of the neighborhood Cover Letter for the community who need it. The specific target of this community service counseling is the creation of a website-based Cover Letter service system and this letter-making system can be implemented directly for the surrounding community. Based on the results of this community service outreach activity, it can be concluded that the website-based application system for the Neighborhood Association Letter is an effective and efficient administrative service solution for the community. Because this system can overcome community problems in making the Cover Letter, that is, without having to meet face-to-face with the Head of the Neighborhood Association and also not waiting for the cover letter to be made. Without realizing it, there are also weaknesses of this system. Such as the decline in the socialization of the Head of the Neighborhood Association because the residents can make an Introduction Letter without having to meet directly with the Head of the Neighborhood Association.